2014
DOI: 10.1093/molehr/gau049
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic regulation of DNA methyltransferases in human oocytes and preimplantation embryos after assisted reproductive technologies

Abstract: DNA methylation is a key epigenetic modification which is essential for normal embryonic development. Major epigenetic reprogramming takes place during gametogenesis and in the early embryo; the complex DNA methylation patterns are established and maintained by DNA methyltransferases (DNMTs). However, the influence of assisted reproductive technologies (ART) on DNA methylation reprogramming enzymes has predominantly been studied in mice and less so in human oocytes and embryos. The expression and localization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 57 publications
2
56
0
Order By: Relevance
“…Ovarian stimulation has been linked to altered imprinted gene methylation in embryos [127,128]. Vitrified mouse oocytes have reduced methylation at imprinted genes in blastocysts, due to reduced DNA methyltransferase expression [129], and this was also found in a human oocyte cryopreservation study [130]. However, a study using human sperm cryopreservation noted no changes to methylation at imprinted genes, spermatogenesis-related genes or MTHFR in the sperm DNA [131].…”
Section: Imprinting Defects and Assisted Reproductive Technologymentioning
confidence: 96%
“…Ovarian stimulation has been linked to altered imprinted gene methylation in embryos [127,128]. Vitrified mouse oocytes have reduced methylation at imprinted genes in blastocysts, due to reduced DNA methyltransferase expression [129], and this was also found in a human oocyte cryopreservation study [130]. However, a study using human sperm cryopreservation noted no changes to methylation at imprinted genes, spermatogenesis-related genes or MTHFR in the sperm DNA [131].…”
Section: Imprinting Defects and Assisted Reproductive Technologymentioning
confidence: 96%
“…It is currently unknown if the mechanism of methylation establishment is the same in humans as several differences have been observed. For example, despite DNMT3L having no catalytic activity, this co-factor is essential for the establishment of all germline-derived maternally methylated imprinted regions in mice, but DNMT3L is not expressed in human oocytes (Petrussa et al 2014) (Table 2). It is therefore assumed that methylated loci in human oocytes recruit DNMT3A directly via their PWWP domain that recognizes H3K36me3 (Dhayalan et al 2010).…”
Section: Methylation Acquisition In the Oocytementioning
confidence: 99%
“…Alternatively, NLRP7-SCMC may ensure the correct cellular localization and nuclear translocation of epigenetic factors during oocyte development. Immunostaining for the two mammalian de novo methyltransferases DNMT3A and DNMT3B has revealed that, like DNMT1, they also have a cytoplasmic localization in human oocytes (Petrussa et al 2014). This suggests that low abundant protein complexes containing the DNMTs may associate to specific DNA sequences possibly by direct interaction with known NLRP7-interacting chromatin regulators YY1 (Mahadevan et al 2014) or ZBTB16 (Singer et al 2015).…”
Section: Nlrp2mentioning
confidence: 99%
“…Reduction of DNMT1 gene expression may cause alteration in the patterns of DNA methylation, resulting in disruption of gene expression, genomic imprinting, and genome stabilization, which can lead to cell death. The expression of DNMT1, seems to be more disturbed in poor quality (fresh and cryopreserved) embryos, in comparison to good quality cryopreserved embryos and delayed fresh embryos (9). It should be noted that, apart from limitations in sample collection, the gene expression analysis on limited number of oocytes was a challenge, due to the small amount of RNA which was extracted.…”
Section: The Effect Of Vitrification On Gene Expression Of Human Oocytesmentioning
confidence: 99%
“…DNMT1 is responsible for the sustainability of the methylation patterns during replication (8). Recently, Petrussa et al showed that DNMT1 was constitutively present in the nuclei of human oocytes and embryos at all stages of preimplantation development until Day 7 after fertilization (9). In mouse, a desirable correlation has been found between aberrant genome-wide DNA methylation patterns, abnormal embryonic development, and preimplantation embryonic loss (10).…”
Section: Introductionmentioning
confidence: 99%